2017
DOI: 10.1111/1759-7714.12490
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of lymph node metastasis in patients with non‐small cell lung cancer ≤ 2 cm in size: A monocentric population‐based analysis

Abstract: AimThis study was designed to determine the risk factors of lymph node metastasis in non‐small cell lung cancer (NSCLC) patients with tumors ≤ 2 cm, using the Shanghai Chest Hospital Lung Cancer Database.MethodsFive hundred and eighteen patients with NSCLC ≤ 2 cm were included in this study, and were classified into lymph node‐positive and lymph node‐negative groups. Univariate and multivariate logistic regression analyses were performed to select the independent risk factors for lymph node metastasis in NSCLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 21 publications
2
29
4
Order By: Relevance
“…17,18 In our study, it was not found to be a relevant factor for nodal involvement in univariate analysis (P = 0.56), which was also observed in the study by Fuwa et al 27 According to multivariate analysis, however, age seemed to be an independent risk factor (OR 0.65, P < 0.0001), which means younger patients were more prone to having lymph node metastases. There was no statistical difference between AD and SCC in the light of the study by Yu et al 28 However, in our study, we found that patients with tumor histology of SCC were much more likely to have lymph node metastases (30.4%) compared with AD patients.…”
Section: Discussioncontrasting
confidence: 76%
“…17,18 In our study, it was not found to be a relevant factor for nodal involvement in univariate analysis (P = 0.56), which was also observed in the study by Fuwa et al 27 According to multivariate analysis, however, age seemed to be an independent risk factor (OR 0.65, P < 0.0001), which means younger patients were more prone to having lymph node metastases. There was no statistical difference between AD and SCC in the light of the study by Yu et al 28 However, in our study, we found that patients with tumor histology of SCC were much more likely to have lymph node metastases (30.4%) compared with AD patients.…”
Section: Discussioncontrasting
confidence: 76%
“…Previous studies have revealed some possible predictive factors for LNM in NSCLC. Yu et al reported several independent risk factors including tumor size, pleural invasion, and carcinoembryonic antigen [33]. Pani et al found that histologic subtypes could be related to lymph node status [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of malignancy‐related death worldwide . Nowadays, radical surgery is regarded not only as the optimal therapeutic option for early‐stage non‐small‐cell lung cancer (NSCLC), but also as the cornerstone of multidisciplinary treatments for more advanced NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Nowadays, radical surgery is regarded not only as the optimal therapeutic option for early-stage non-small-cell lung cancer (NSCLC), but also as the cornerstone of multidisciplinary treatments for more advanced NSCLC. [4][5][6][7] Since the 1990s, single lobectomy via video-assisted thoracoscopic surgery (VATS), a minimally invasive procedure providing access to the chest cavity, has been developed as a modern surgical modality for operable NSCLC, offering more advantages than conventional thoracotomy in terms of the cosmetic wounds, pain and stress control, preservation of pulmonary function, and enhanced recovery. 6,[8][9][10][11][12] Despite advances in surgical techniques and perioperative care, however, the morbidity rate after VATS lobectomy remains 26.2-36.3%.…”
Section: Introduction Rationalementioning
confidence: 99%